Inovações no mercado financeiro brasileiro: os bancos tradicionais e o surgimento das fintechs - Andrighetti, Caroline Lovison (My University, 2021)
The national financial market plays a relevant role for the country's growth and development. The services of intermediation of resources between investors and borrowers allow the proper flow of the economy and promote an increment in the level of economic welfare. The accelerated emergence of new technologies point to an increasingly digital future, mainly due to the rise of fintechs in the financial market. Therefore, considering the importance of this market and technological changes, this paper aims to analyze the innovations in the Brazilian financial market with the emergence of fintechs and the relationship with traditional banks. The methodology used is descriptive historical theory for chapter two, descriptive theoretical research for chapter three and, finally, performing a descriptive analysis approach in chapter four. The analysis carried out validated the hypothesis that the insertion of fintechs in the financial market through the use of high technologies accelerated the digital transformations in traditional banks, making them invest more in banking technology and modify teir way of operating in order to remain competitive in the sector. [resumo fornecido pelo autor]
O mercado financeiro nacional desempenha função relevante para o crescimento e desenvolvimento do país. Seus serviços de intermediação de recursos entre investidores e tomadores permitem o devido fluxo da economia e promovem o aumento do nível de bem-estar econômico. O surgimento acelerado de novas tecnologias apontam para um futuro cada vez mais digital, principalmente em razão da ascensão das fintechs no mercado financeiro. Diante disso, considerando a importância desse mercado e das transformações tecnológicas, o presente trabalho tem como objetivo analisar as inovações no mercado financeiro brasileiro com o surgimento das fintechs e a relação com os bancos tradicionais. A metodologia utilizada é a teórica histórica descritiva para o capítulo dois, pesquisa teórica descritiva para o capítulo três e, por fim, realizando uma abordagem de análise descritiva no capítulo quatro. A análise realizada validou a hipótese de que a inserção das fintechs no mercado financeiro a partir do uso de altas tecnologias aceleraram as transformações digitais nos bancos tradicionais fazendo com que estes invistam mais em tecnologia bancária e modifiquem sua forma de atuação a fim de se manterem competitivos no setor. [resumo fornecido pelo autor]
Keywords: Economia; Inovações tecnológicas; Mercado financeiro; Bancos